O ensino da divisão matemática nas turmas de 6º ano no ensino fundamental: um relato de experiência em uma escola da zona rural no município de Santarém-Pa - SANTOS, Raimundo José Fonseca dos (Universidade Federal do Oeste do Pará, 2024)
This work is the result of an experience report that was carried out with the 6th grade students of the Sagrada Familia Municipal School, located in the rural area of the municipality of Santarém-PA. The present work has the theme "The Teaching of the Mathematical Division" in the context of a school of the field. Aware of the importance of the role of mathematics in the development of the individual; the present work presents reflections and proposals to soften the difficulties of school learning and aims to subsidize elements that may contribute to the improvement of the understanding of the teaching-learning process of Mathematics, but precisely the division in the classroom. The applied methodology was the field research with application of the teaching practice and the bibliographical research, to better theoretical foundation of the research. The final results of this work showed that mathematics has gained space among elementary school students, and it was possible to verify by the practical activities that were carried out with the group of the 6th year, the contact with the concrete materials, somehow, encouraged students to participate in all proposed activities. In this sense, it is necessary to take into account that in order to develop and stimulate students to knowledge and improvement in the mathematical division, it is necessary that the teacher of this discipline plays a very important role in the learning process.